Neutron Activation Analysis of Surface Sediments From Dardanelles - Ilgar, R.; Akyuz, T.; Mukhamedshina, N.; Akyuz, S.; Mirsagatova, A.A.; Sari, E. (Asian Journal of Chemistry, 2012)
Some surface sediments, collected from 7 sampling sides of the Dardanelles and 13 sampling sited of creeks in the area of surrounding of the Dardanelles were analyzed quantitatively by neutron activation analysis (NAA) and concentrations of Na, Al, K, Ca, Sc, Fe, Co, As, Rb, Sr, Y, Sb, Cs, Hf, U, Th and rare earth elements (La, Ce, Sm, Eu, Dy, Yb, Lu) were determined. Uranium and thorium results were found to be compatible with those given in the literature for marine sediments. Results indicated correlations between Rb and Sr (r = 0.8542), Th and Ce (r = 0.8131), Th and La (r = 6371), Th and Sm (r = 4756) in the creek sediments. These correlations were find to be r = 0.5361 (Rb and Sr), r = 0.8571 (Th and Ce), r = 7397 (Th and La), r = 0.9045 (Th and Sm), respectively, in the marine sediments.